2013
DOI: 10.1890/es12-00270.1
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of groundwater pumping and climate variability on groundwater availability in the Rio Grande Basin

Abstract: Abstract. Groundwater is a critical resource for sustainable economic growth in an arid and semi-arid region such as the Rio Grande Basin because it provides water for municipal, industrial, and domestic, and agricultural users. The water is also important for the health of riparian ecosystems in the Rio Grande basin. Historic groundwater pumping has resulted in large groundwater level drawdown, water quality deterioration, depletion of surface water and subsidence in El Paso/Ciudad Juarez area, which in turn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 47 publications
0
50
0
1
Order By: Relevance
“…Generally, though, impacts of changing demands on groundwater systems, whether due directly to climate changes or indirectly through changes in land use or surface-water availability and management, are likely to cause more immediate changes in groundwater availability (Taylor et al 2012, Sheng 2013. Changes in recharge and resulting changes in storage may be more subtle and take longer to emerge.…”
Section: Groundwatermentioning
confidence: 99%
“…Generally, though, impacts of changing demands on groundwater systems, whether due directly to climate changes or indirectly through changes in land use or surface-water availability and management, are likely to cause more immediate changes in groundwater availability (Taylor et al 2012, Sheng 2013. Changes in recharge and resulting changes in storage may be more subtle and take longer to emerge.…”
Section: Groundwatermentioning
confidence: 99%
“…Gelhar and McLin (1979) showed that total dissolved solids (TDS) in the alluvium aquifer increases from ~1000 mg/L in the northern Mesilla Basin to 8000 mg/L in the southern basin. The alluvium aquifer is recharged by seepage from the Rio Grande and irrigation Hiebing et al | Gravity and groundwater studies of the southern Mesilla Basin GEOSPHERE | Volume 14 | Number 4 water (Sheng, 2013). Individual wells with high salinity or iron values appear to tap abandoned river channels and swamp or bog deposits (Arunshankar, 1993).…”
Section: Hydrological Frameworkmentioning
confidence: 99%
“…Individual wells with high salinity or iron values appear to tap abandoned river channels and swamp or bog deposits (Arunshankar, 1993). The Rio Grande alluvium is hydrologically connected to the underlying aquifers within the Santa Fe Group, leading some researchers (e.g., Sheng, 2013) to propose that use of Rio Grande water and saline groundwater from the Rio Grande aquifer for flood irrigation has led to the increased salinity observed within the Santa Fe Group aquifers in the southern Mesilla Basin.…”
Section: Hydrological Frameworkmentioning
confidence: 99%
“…The deeper Hueco Bolson and large portions of the Mesilla Bolson are primarily "fossil" deposits of water with little or no recharge. Thus, drawdown represents withdrawals against current and future reserves [8]. This scenario is being repeated not only in other river basins of the southwestern U.S., but also in other arid and semi-arid regions of the world that are dependent primarily on a desert river basin and its associated aquifers to meet the needs of irrigated agriculture, as well as growing urban populations [37].…”
Section: Case Study Descriptionmentioning
confidence: 99%
“…This part of the Rio Grande basin can be characterized as having limited and dwindling supplies of water, increasing demands for water from multiple sectors, and a segmented governance system spanning two U.S. states and two countries [5]. On top of this, the region faces a number of drivers of change, including: (1) climate change that is impacting both (a)water supply, through reduced snowpack and timing of flows in the headwaters, and (b) demand, through increasing temperatures and greater evapotranspiration; (2) agricultural practices and trends, especially increasing production of high water demand crops and greater reliance on groundwater of marginal quality for irrigation; (3) urban growth, impacting water demand and quality (through wastewater discharges); and (4) growing demand for environmental services, such as riparian habitat and environmental flows [5][6][7][8]. In this mix of changing conditions, the prevailing water governance in the region was developed for the situation that existed about 100 years ago, and is characterized by rigid water institutions, weak participation, division by artificial borders, and quiet but protracted conflicts [5].…”
Section: Introductionmentioning
confidence: 99%